Impact of Lean Manufacturing Practices on Firms’ Sustainable Performance: Lean Culture as a Moderator - Iranmanesh, Mohammad; Zailani, Suhaiza; Hyun, Sunghyup; Ali, Mohd; Kim, Kwangyong (MDPI, 2019)
Nowadays, manufacturing firms are pressured by governments, non-governmental organizations and customers to operate in a sustainable manner. Although lean practices may provide environmental, social, and financial benefits to firms, their effect on sustainable performance is ambiguous. The aim of this study is to examine the effect of lean manufacturing practices on firms' environmental performance by considering lean culture as a moderator. Data were gathered through a survey of 187 manufacturing firms in Malaysia and were analyzed using the partial least squares technique. The results indicate that process and equipment, product design, supplier relationships, and customer relationships have a positive and significant effect on sustainable performance. It is also interesting to observe that lean culture positively moderated the effects of process and equipment and supplier relationships on sustainable performance. These results have important implications for enhancing the sustainable performance of manufacturing firms through lean manufacturing practices. © 2019 by the authors.